Muscular Arrangement and Muscle Attachment Sites in the Cervical Region of the American Barn Owl (Tyto furcata pratincola) - Boumans, Mark L. L. M.; Krings, Markus; Wagner, Hermann (PLOS ONE, 2015)
Owls have the largest head rotation capability amongst vertebrates. Anatomical knowledge of the cervical region is needed to understand the mechanics of these extreme head movements. While data on the morphology of the cervical vertebrae of the barn owl have been provided, this study is aimed to provide an extensive description of the muscle arrangement and the attachment sites of the muscles on the owl’s head-neck region. The major cervical muscles were identified by gross dissection of cadavers of the American barn owl (Tyto furcata pratincola), and their origin, courses, and insertion were traced. In the head-neck region nine superficial larger cervical muscles of the craniocervical, dorsal and ventral subsystems were selected for analysis, and the muscle attachment sites were illustrated in digital models of the skull and cervical vertebrae of the same species as well as visualised in a two-dimensional sketch. In addition, fibre orientation and lengths of the muscles and the nature (fleshy or tendinous) of the attachment sites were determined. Myological data from this study were combined with osteological data of the same species. This improved the anatomical description of the cervical region of this species. The myological description provided in this study is to our best knowledge the most detailed documentation of the cervical muscles in a strigiform species presented so far. Our results show useful information for researchers in the field of functional anatomy, biomechanical modelling and for evolutionary and comparative studies.